Influence of the interlaced holes on crack propagation behavior under impact loads. (May 2022) - Gao, Weiting; Zhu, Zheming; Wang, Meng; Ying, Peng; Wang, Fei; Niu, Caoyuan; Zhang, Xianshang
Highlights: An Improved Single Cleavage Semicircle Compression specimen were proposed. The whole process of crack propagation from macro and micro was analyzed. The influence mechanism of interlaced holes on crack propagation was analyzed. The holes affect the crack propagation by the re-release of deformation energy storage. Abstract: Hole defects are common defects in natural materials, which obviously affect crack propagation. In this paper, an Improved Single Cleavage Semicircle Compression specimen made from polymethyl methacrylate with a pre-crack and two holes were used. In order to analyze the influence of the interlaced holes on crack propagation, a series of dynamic experiments were carried out utilizing the Split-Hopkinson pressure bar system with crack propagation gauges. In addition, the influence mechanism of interlaced holes on crack propagation was studied by numerical simulation. A good agreement was achieved between the simulation and experimental results. It was concluded that interlaced holes have a restraining and guiding effect on crack propagation. As the distance between two holes increases, the effect becomes weak. Under the action of stress waves, the two interlaced holes deform and form a pressure zone when the crack passes through the hole area. The phenomenon of crack arrest and crack deflection depends on the asymmetric distribution of the pressure zone.